Self-control and self-management as indicators of professional self-awareness of the subject of service activity - Sharafutdinova, N. V. (Вестник университета, 2025)
Ensuring training of employees to perform tasks of various complexity, to form their professional reliability and readiness for long-term performance of service activities, awareness of their place and responsibility for supporting the policy pursued by the Russian Federation (hereinafter referred to as RF) are priority goals and objectives in ensuring activities of the internal affairs bodies of the RF. In modern times, due to the increase of geopolitical and social conflicts, new requirements for training of law enforcement officers, assessing their mental and physical capabilities emerge. This scientific article contains theoretical and empirical materials related to the study of self-control and self-management as indicators of professional self-awareness. The relevance of the scientific problem is related to the need for further development and implementation of a research programme on the dynamic nature of the professional self-awareness, for characterisation of  the system of  structural components of the phenomenon in question. The novelty of the research lies in the study of self-control and self-management as indicators of the professional self-awareness formed under the influence of professional environment, activity of the subject in the conditions of official business. The article presents the results of a psychodiagnostic study of the indicators of the self-control and self-management of subjects of official activity using a correlation analysis of the links between them.